2006
DOI: 10.1111/j.1464-5491.2006.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of calcitriol and nicotinamide on residual pancreatic β‐cell function in patients with recent‐onset Type 1 diabetes (IMDIAB XI)

Abstract: At the dosage used, calcitriol has a modest effect on residual pancreatic beta-cell function and only temporarily reduces the insulin dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 18 publications
1
79
0
2
Order By: Relevance
“…This could influence the autoimmue pathology of Type 1 diabetes, and could ameliorate low-grade chronic inflammation that has been implicated in insulin resistance in Type 2 diabetes [11]. Vitamin D may also stimulate insulin release by pancreatic b-cells [12,13]. Elevated parathyroid hormone levels, consequent on low vitamin D levels, have also been implicated in impaired insulin release from pancreatic b-cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…This could influence the autoimmue pathology of Type 1 diabetes, and could ameliorate low-grade chronic inflammation that has been implicated in insulin resistance in Type 2 diabetes [11]. Vitamin D may also stimulate insulin release by pancreatic b-cells [12,13]. Elevated parathyroid hormone levels, consequent on low vitamin D levels, have also been implicated in impaired insulin release from pancreatic b-cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pittoco et al reported the results of an interventional trial in children with newly diagnosed type 1 diabetes, in which the patients were administered calcitriol or nicotinamide in order to preserve beta-cell function. Even though there was a decrease in the insulin requirements at 3 and 6 months in the calcitriol treated group, at the end of the first year there was no difference between the C-peptide levels or hemoglobin A1c between the two groups (Pitocco et al, 2006). Bizzarri et al investigated whether supplementation with calcitriol in recent onset autoimmune diabetes has a protective effect on the pancreatic beta cells and found that, at the doses used in the study, calcitriol did not confer protection against the autoimmune destruction of the beta cells (Bizzarri et al, 2010).…”
Section: Clinical Studies -Vitamin D and Type 1 Diabetesmentioning
confidence: 90%
“…Here we are limited to small interventions and animal studies. In type 2 diabetes very high doses of 25-(OH)D have been administered, but the data are confusing, whereas in type 1 diabetes 1,25-(OH)2D has mainly been given, with little or no effect on C-peptide preservation in newly diagnosed type 1 patients [7,8]. What about NOD mice?…”
Section: Cyp27b1mentioning
confidence: 99%